Professional identity and university teaching training: A construction process from the students overview - Miranda Cervantes, Giselle (2019)
This article presents a longitudinal study developed between 2014-2017 among three groups of DEB students at Diploma level of Pedagogy program in I & II cycles, Special Education and Preschool Education at División de Educación Básica (DEB), Centro de Investigación en Docencia y Educación (CIDE), Universidad Nacional, Costa Rica, as part of the project Identidad Docente: Resignificando la labor profesional. Within a methodological inquiry phase, a questionnaire was applied in 2014 and then again in 2017 to the same groups of students regarding their personal choice of a major in teaching education, as well as whether they had received family support regarding that decision. The results indicate that students in the three participant groups identify themselves with being teachers, and this identity becomes stronger as they move ahead in their university education. Differences are shown within the three program groups in terms of the selection of education as a profession and the perception of social recognition of this profession. The conclusions highlight that it is necessary for university faculties and centers to contribute towards teaching education and professional development of Costa Rican teachers.